Application of local projections in the monetary policy in Brazil. Issue 13 (29th July 2018) - Carcel, Hector; Gil-Alana, Luis A.; Wanke, Peter
ABSTRACT: This article examines the relationship between selected monetary aggregates and inflation and output in Brazil. Impulse responses under VAR and local projections were used to discover the leading or lagging role of the monetary aggregates. In addition, the information provided by the monetary aggregates as predictors of output and inflation was examined. This was assessed by examining their predictive power for subsequent observations on an in-sample basis. Overall, the results indicate that in order to control inflation rates, Brazilian authorities should focus on restricting money supply rather than increasing interest rates.